Factors Associated with Teacher’s Attitude to Teach in an Inclusive Education Environment - Fitria, Ika; Permatasari, Dian Putri; Prasetyo, Ridwan Aji Budi (Indonesian Journal of Disability Studies, 2025)
The interaction between self-efficacy and several demographic variables is still rarely explored in the context of explaining teacher’s attitude toward inclusive education practices. This paper therefore aims to investigate the relationship between these variables and their interaction in explaining teacher’s attitude. Ninety-five teachers participated in our study by completing questionnaires and psychological scales capturing their self-efficacy, demographic information, and attitude towards inclusive education. The results suggest that higher self-efficacy may predict higher score in attitude (R2 = 0.045, F(1, 93) = 4.41, p < 0.05), yet demographic variables cannot significantly act as predictors (R2 = 0.13, F(13, 81) = 0.89, p = 0.56). This study brings an important notion to prioritize strategies to increase teacher self-efficacy to foster the implementation of inclusive education practices.